Pembentukan Komunitas Virtual di Platform X: Studi Kasus Reaksi Komunitas Marah-Marah Atas Penganugerahan Gelar H.C. Kepada Raffi Ahmad - Anahiz, Sarah; Hakim, Syiefa Alaida; Ramadhan, Muhammad Fitra Aulia; Azhari, Shinta Dwi; Ilham, Muhammad Fakhriansyah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The conferral of this honorary title has sparked mixed reactions from the public, particularly on social media platforms, where diverse opinions are widely expressed. One of the most vocal groups is the virtual community known as the "Angry Community." This group consists of individuals who disagree with or are even outraged by the decision to grant the title. They utilize Platform X to voice their disapproval, share critiques, and engage in discussions about the meaning and relevance of honorary titles (H.C.), particularly in this case involving a public figure like Raffi Ahmad. Data was collected using three primary techniques: participatory observation, in-depth interviews, and document analysis. Participatory observation was conducted to monitor interactions within the community directly, while in-depth interviews with community members, social media experts, and cultural observers aimed to provide deeper insights. The findings reveal that solidarity within this virtual community is built upon shared values, such as respect for academia, disapproval of the blending of the celebrity and academic worlds, and appreciation for formal learning processes. The community’s reactions are not merely a form of protest but also reflect their respect for these principles.